Comparison of HLA-A, -B and -DRB1 Loci Polymorphism between Kidney Transplants of Uremia Patients and Healthy Individuals in Central China - Shang, Wenjun (PLoS One, 2016)
Chronic kidney disease is becoming a global public health problem, which will usually cause uremia at the end stage of chronic kidney failure. So far, kidney transplant is the most effective and proper therapy for uremia, however, the short supply of matched donor kidney has been a persistent bottleneck for transplantation. HLA matching of HLA-A, -B and -DRB1 loci is very important for the allocation of kidney transplants. In this study, we investigated genotypes of HLA-A, -B and -DRB1 loci based on 1,464 uremia patients and 10,000 unrelated healthy individuals in Henan province of China, and compared the frequency distribution of these HLA alleles and corresponding haplotypes between patient and healthy groups. We detected 23 HLA-A, 49 HLA-B and 17 HLA-DRB1 alleles in total. The predominant alleles of HLA-A, -B and -DRB1 loci in patients are the same as those in healthy group. The seven most frequent alleles account for about 87%, 50%, and 77% at HLA-A, -B and -DRB1 loci, respectively. The haplotypes (combinations of HLA-A, -B, and -DRB1) with significantly different frequency between patients and controls mostly account for less than 1%. Overall, this suggests that HLA matching is not a potential difficulty for kidney transplant of uremia patients. However, three of the top seven frequent HLA-DRB1 alleles have a significantly different distribution in patients and controls, while only one alleles for HLA-B and zero for HLA-A loci. These HLA-DRB1 alleles may be closely associated with uremia. This study sheds new lights on the composition and difference of HLA genotypes in uremia patients and healthy populations in Central China that can serve as a guide to HLA matching for kidney transplants and a resource for HLA typing-related studies.